Applications of ultrasonography in cattle reproduction - AMIRIDIS (Γ.Σ. ΑΜΟΙΡΙΔΗΣ), S. G.; LYMBEROPOULOS (Α. ΛΥΜΠΕΡΟΠΟΥΛΟΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Ultrasonography is becoming a useful diagnostic toolin the field of cattle pathophysiology, aiding to meet the demands of the expanding cattle breeding. Transrectal ultrasonography is a rapid, reliable and safe technique for both the animal and the operator. With the use of ultrasonography in research, the hypothesis concerning the wave - like pattern of follicular growth has been confirmed. In addition it has been proved that follicular growth, development and regression continue during early pregnancy. The application of ultrasonographic techniques in concert with modern biotechnology, boosted the production of embryos from genetically superior cows and prepubertal heifers and indirectly solved the problem of infertility in valuable animals. In clinical practice, the use of ultrasonography for early pregnancy diagnosis and for diagnosis of pathologic conditions which lead to prolonged postpartum anoestrous, makes a considerable contribution to the reduction of calving interval. In this review basic physical principles of ultrasonography are described and selected applications in the field of cow reproduction are discussed.